Implementasi Metode Muhadatsah dalam Meningkatkan Keterampilan Berbicara Bahasa Arab di Pondok Modern Darussalam Gontor Putra 2 Ponorogo - Fatana Bira Suli; Nuraini Nuraini; Devid Dwi Erwahyudin (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the implementation of the muhadatsah method in improving the Arabic speaking skills of students at Pondok Modern Darussalam Gontor Putra 2 in Ponorogo. This study employs a qualitative method in which data were collected through field research. The research subjects consisted of Arabic language teachers at Pondok Modern Darussalam Gontor Putra 2. Data were collected through direct observation, in-depth interviews, and documentation related to the learning process. Data analysis was conducted comprehensively to understand the interaction process between teachers and students as well as the method’s influence on the theoretical understanding and practice of the Arabic language. The research results indicate that the muhadatsah method at Pondok Modern Darussalam Gontor Putra 2 is implemented systematically through language activities, including: determining the muhadatsah theme, vocabulary (mufrodat) instruction, constructing sentences in Arabic, direct conversation practice, and intensive supervision by the Language Advisory Council (LAC). This program helps improve students’ speaking skills through the talaqqi or ilqo’iyyah method, daily communication practice, natural vocabulary enrichment, and the development of a positive mindset and self-confidence in Arabic. Furthermore, this program plays a crucial role in fostering a disciplined language environment through a strict monitoring system, the imposition of consequences, and the exemplary conduct of dormitory staff and teachers. Thus, the implementation of the muhadatsah method plays a significant role in improving speaking skills and establishing a strong Arabic communication culture at Pondok Modern Darussalam Gontor Putra 2.